Occurrence of polycyclic aromatic hydrocarbons (PAHs) carcinogen in Indonesian commercial goat satay. Issue 1 (November 2021) - Saputro, E; Radiati, L E; Warsito, W; Rosyidi, D
Abstract: This study aimed to investigate the carcinogen content of polycyclic aromatic hydrocarbons (PAHs) in commercial charcoal grilled goat satay. Twenty-one portions of commercial raw goat satay and charcoal grilled goat satay samples were obtained from 4 restaurants which are the largest, well-known, and 15-55 years old goat satay restaurant in Batu Municipality, East Java. Sampling of 2 goat satay types (goat satay without sliced fat and goat satay with sliced fat) was carried out 3 replications in 3 consecutive weekends where many tourists visited. The results showed that the temperature of wood charcoal for grilling commercial raw goat satay in various satay restaurants ranged 486.833-548.300 o C with a grilling duration of 2-5.5 minutes and grilling distance of 0.5-2 cm. The weight of raw goat satay for a serving (10 skewers) ranged 144.000-194.000 g and after grilling the weight ranged 97.333-148.000 g. Total natural antioxidant activity (Dipheny-picrylhydrazyl, DPPH), fat content and moisture content of raw goat satay with sliced fat and without sliced fat reached up to 36.661 and 34.124%; 13.440-26.100% and 1.5-6.305%; 57.940-66.385% and 71.530-76.810%, respectively. Benzo(a)pyrene (BaP), the only type of PAHs that is carcinogenic, for charcoal grilled goat satay with sliced fat and without sliced fat in various satay restaurants, ranged from not detected to 6.330 mg/kg and not detected to 0.773 mg/kg, respectively. The levels of BaP in charcoal grilled goat satay in several satay restaurants exceeded the safety limit by National Agency of Drug and Food Control (NA-DFC) of Republic Indonesia. Benzo(a)antharacene (BaA) and pyrene (Pyr) were detected in all grilled goat satay samples in various satay restaurants. Whereas, phenanthrene (Phe), acenaphthene (Acp) and naphthalene (Nap) were not detected in all grilled goat satay samples in various satay restaurants. The conclusion of our study was that the commercial charcoal grilled goat satay that are sold in Batu municipality contains PAH, especially the carcinogenic B(a)P. Therefore practical mitigation efforts are needed for producers to reduce and prevent the formation of carcinogenic B(a)P in commercial charcoal grilled goat satay.